A DNS study of the effects of temperature non-uniformity and turbulence on an auto-ignition process in a homogeneous n-heptane/air mixture - Takashi ISHIHARA; Takamasa ITO; Takashi MIKI; Katsunori YOSHIMATSU; Atsushi TERAJI (Nihon Kikai Gakkai ronbunshu, 2014)
We examine the effects of temperature non-uniformity and turbulence on homogeneous charge compression ignition (HCCI) of a homogeneous n-heptane/air mixture, using three-dimensional direct numerical simulations of the mixture flows. We use a reduced chemical reaction model for the HCCI combustion. Time evolutions of the flows are obtained under the initial conditions having three different initial velocity fluctuations at 4.0 MPa and with temperature fluctuation around 781 K. Heat-release by the low-temperature oxidation, a key reaction in the ignition process, is analyzed along the trajectories of the temperature gradients, using dissipation-elements decomposition of the temperature fields. It is shown that the high heat-release rate occurs in the membrane-like regions where the temperature is about 870 K. The membrane-like regions move along the trajectories from high to low temperature. The analysis on the trajectories shows that the conditionally averaged moving speed and thickness of the regions are decreasing functions of the magnitude of temperature gradient. When the velocity fluctuation is strong, the turbulent flow is found to play a key role in retarding the ignition: The turbulent flow reduces the maximum temperature and slows down the averaged moving speed of the membrane-like regions.